Damage to the historic town of Staufen (Germany) caused by geothermal drillings through anhydrite-bearing formations - Sass, Ingo; Burbaum, Ulrich (Acta Carsologica, 2010)
<span style="line-height: 115%; font-family: "Times New Roman","serif"; font-size: 9pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Shallow geothermal systems for the heating and cooling of buildings will play an important role in the future renewable energy supply. Especially in dense settlements the geothermal energy utilization for facility heating and cooling is very promising. Therefore, it is important to analyse the damage to Staufen im Breisgau (Germany). In September of 2007, seven geothermal borehole heat exchanger (BHE) drillings were performed in a small square directly adjacent to the 16<span style="line-height: 115%; font-family: "Times New Roman","serif"; font-size: 5pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">th <span style="line-height: 115%; font-family: "Times New Roman","serif"; font-size: 9pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">century town hall in the centre of the town. These led to enormous structural damage to buildings as a function of four different geological parameters: artesian groundwater, two interacting karst formations, strong tectonization, and a swellable anhydrite formation. Some weeks after termination of the well construction, uplift started, and recently (March 2010) reached a magnitude of approximately 26 cm. Actually, some 250 buildings (March 2010) are involved; showing cracks, tilting, and other effects of the differential swelling movements beneath the foundations. Surface uplifts with rate up to 10 mm/month have been determined using high-resolution spaceborne radar data and radarinterferometric techniques. These amplitudes correlate with data from benchmarks of terrestrial geodetic surveyng. Besides the uplift due to the swelling processes, future problems could arise from the fact that the gypsum formed from the swelled anhydrite is soluble in water. Thus, sinkholes and other karst related phenomena may occur.